Analysis of particulate matter and carbon monoxide emission rates from vehicles in a Shanghai tunnel. (May 2020) - Yang, Qinghai; Shen, Henggen; Liang, Zhen
Highlights: Real-time vehicle-specific ratio power distribution of the fleet in Yan'an tunnel. Change in Particulate Matter and Carbon Monoxide Emission Rates over years. Model of motor vehicle emissions simulator in predicting the pollutant emission factors. Human Health Damages indicate hazardous pollutants in the tunnel ventilation flow. Complementary ventilation in pollution reduction and energy efficiency operation. Abstract: Underground road tunnels are becoming increasingly prevalent in cities as a means to alleviate ground traffic congestion, which in turn leads to air pollution near tunnel exits and an increase in the power consumption of ventilation systems. To investigate the characteristics of vehicle exhaust pollutants and human health damages (HHDs), we conducted tests in a typical Shanghai underground tunnel, in which real-time wind speeds, traffic volume rates, vehicle velocities, and traffic distribution were recorded. The prediction model of emission factors with motor vehicle emissions simulator (MOVES) was verified by comparing test results, the UNEP/SETAC toxicity (USEtox) Life Cycle model was adopted to assess the HHDs due to CO, PM2.5, and PM10, and the air-exchanging ventilation was analysed for potential pollution reduction. Results showed emission rates were reducing yearly and could be predicted with MOVES, PM10 had a greater impact on human health than PM2.5 in the tunnel ventilation, and complementary ventilation could improve the tunnel ventilation effects. The survey findings can be used to conduct a new quantitative assessment and an efficient control method for air pollution in city tunnel systems, and in turn improve the energy efficiency of existing underground tunnels.